Seated limits-of-stability of athletes with disabilities with regard to competitive levels and sport classification - Santos, P. B. R.; Vigario, P. S.; Mainenti, M. R. M.; Ferreira, A. S.; Lemos, T. (Scandinavian Journal of Medicine & Science in Sports, 2017)
We aimed to evaluate the influence of wheelchair rugby (WR) classification and competitive level on the seated limits of stability of athletes with disabilities. Twenty-eight athletes were recruited from international and national level WR teams. Athletes were distributed into three groups per their classification: low-point (0.5-1.5-point); mid-point (2.0-2.5-point); and high-point (3.0-3.5-point). Athletes were asked to sit on a force platform placed upon a wooden block and to lean the body as far as possible in eight pre-defined directions. Center of pressure (COP) coordinates were calculated from the ground reaction forces acquired with the force platform. Seated limits of stability (LoS) were computed as the area of ellipse adjusted to maximal COP excursion achieved for the eight directions. Our main results were that no difference in the LoS was observed between international and national level players (p=0.722). However, LoS were 1.7 times greater in players from the high-point group than from the low-point group (p=0.030). The mid-point group was not different from the high- or low-point groups (p>0.149). In summary, LoS are influenced by WR classification but not competitive level. Our results highlight the LoS as a training-resistant, valid measure of a specific impairment, potentially contributing to the development of an evidence-based WR classification.